2017
DOI: 10.1108/cr-07-2015-0066
|View full text |Cite
|
Sign up to set email alerts
|

Are KIBS beneficial to international business performance

Abstract: Purpose The purpose of this paper is to test whether knowledge-intensive business services (KIBSs) contribute to international business activity. In line with studies from the servitization, the territorial competitiveness and the global value chain realm, it can be hypothesized that if KIBS consumption has a positive effect on business competitiveness, a correlation is discernible between “intensity of KIBS uptake” and “turnover and export performance at industrial sector level”. Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Lafuente et al analyse the renaissance of local manufacturing sectors by studying role of local KIBs in increasing competitiveness and employment at a territorial level, subsequently producing a virtuous circle defined as "territorial servitization". These results are in line with Kamp and Ruiz de Apodaca (2017), who show how the interaction between manufacturing firms and KIBS increases total exports and turnover on a regional level. This line of research on the effect of territorial servitization is important, as it ultimately provides policy tools to regional and national governments to stimulate service innovation in the region.…”
Section: Interaction Between Manufacturing and Kibssupporting
confidence: 91%
“…Lafuente et al analyse the renaissance of local manufacturing sectors by studying role of local KIBs in increasing competitiveness and employment at a territorial level, subsequently producing a virtuous circle defined as "territorial servitization". These results are in line with Kamp and Ruiz de Apodaca (2017), who show how the interaction between manufacturing firms and KIBS increases total exports and turnover on a regional level. This line of research on the effect of territorial servitization is important, as it ultimately provides policy tools to regional and national governments to stimulate service innovation in the region.…”
Section: Interaction Between Manufacturing and Kibssupporting
confidence: 91%
“…This research line opens an interesting approach to contextualize PSI within the International Business field, where Vendrell-Herrero et al (2018b) demonstrated how cross-border strategic alliances increase the positive PSI-performance relationship. Also, Kamp and Ruiz de Apodaca (2017) found evidence that KIBS are beneficial to international business performance. Finally, the role of KIBS in understating the complexities behind PSI-performance relationship is a topic of increased interest that has inspired recent work Gomes et al, 2018;Lafuente et al, 2017).…”
Section: Other Outcome Variables: Innovation Performance Market Knowmentioning
confidence: 99%
“…Identifying these benefits extends previous contributions to territorial servitization which focused on employment, resilience, or start-up rates as territorial benefits (e.g. Lafuente et al, 2017;Kamp & Ruiz de Apodaca, 2017;Vendrell-Herrero & Wilson, 2017). In our work, the argument that servitization strengthens employment has been specified for each phase in the industry life cycle.…”
Section: Implications For Academic Researchmentioning
confidence: 68%
“…Servitization also leads to knowledge-intensive services being provided by the manufacturing industry itself. Accordingly, the extension of services in manufacturing companies and industries leads to service competencies, which strengthen production and employment in the specific geographical region (Kamp & Ruiz de Apodaca, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation